Isolated Murine Brain Model for Large-Scale Optoacoustic Calcium Imaging - Gottschalk, Sven; Degtyaruk, Oleksiy; Mc Larney, Benedict; Rebling, Johannes; Deán-Ben, Xosé Luis; Shoham, Shy; Razansky, Daniel (Frontiers in Neuroscience, 2019)
Real-time visualization of large-scale neural dynamics in whole mammalian brains is hindered with existing neuroimaging methods having limited capacity when it comes to imaging large tissue volumes at high speeds. Optoacoustic imaging has been shown to be capable of real-time three-dimensional imaging of multiple cerebral hemodynamic parameters in rodents. However, optoacoustic imaging of calcium activity deep within the mammalian brain is hampered by strong blood absorption in the visible light spectrum as well as lack of activity labels excitable in the near-infrared window. We have developed and validated an isolated whole mouse brain preparation labelled with genetically encoded calcium indicator GCaMP6f, which can closely resemble in vivo conditions. An optoacoustic imaging system coupled to a superfusion system was further designed and used for rapid volumetric monitoring of stimulus-evoked calcium dynamics in the brain. Our new technique captures calcium fluxes as true three-dimensional information across the entire brain with temporal resolution of 10ms and spatial resolution of 150µm, thus enabling large-scale neural recording at penetration depths and spatio-temporal resolution scales not covered with any existing neuroimaging techniques.